KOMPARASI ARCS DAN PBL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PADA SISWA SEKOLAH DASAR - Ridwan, Nurhudayana; Kaharuddin; Suardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study employed a Counterbalanced Design research approach using two instructional models: the ARCS Learning Model and Problem-Based Learning (PBL). The research was conducted in the second semester of the 2023/2024 academic year. The population consisted of fifth-grade students from Cluster V elementary schools in Panakukang District. The sample was selected randomly using a random sampling technique from two schools: UPT SPF SD Inpres Panyyikokang 1 and SD Inpres Panyyikokang 2. Data were collected through observation, tests, and documentation. The data were analyzed using inferential statistical analysis, including tests of normality, homogeneity, and hypothesis testing through the Independent Sample T-Test. The results showed that both instructional models significantly improved students’ learning outcomes in Pancasila Education among fifth-grade students. Students demonstrated increased understanding of the Pancasila Education material. Although there was no substantial significant difference between the ARCS and PBL models in terms of learning outcomes, both were effective in enhancing students’ comprehension. This study provides a clearer understanding of the effectiveness of each instructional model in improving Pancasila Education learning outcomes among fifth-grade students in Cluster V, Panakukang District.